Generation of Transgenic Mosquitoes Harboring a Replication-Restricted Virus - Shinzawa, Naoaki; Kashima, Chisako; Aonuma, Hiroka; Takahashi, Kei; Shimojima, Masayuki; Fukumoto, Shinya; Saiki, Erisha; Yamamoto, Daisuke S.; Yoshida, Shigeto; Matsuoka, Hiroyuki; Kawaoka, Yoshihiro; Kanuka, Hirotaka (Frontiers in Tropical Diseases, 2022)
Live microbe vaccines are designed to elicit strong cellular and antibody responses without developing the symptoms of the disease, and these are effective in preventing infectious diseases. A flying vaccinator (also known as a flying syringe) is a conceptual, genetically engineered hematophagous insect that is used to deliver vaccines such as an antigen from a parasite produced in mosquito saliva; bites from such insects may elicit antibody production by immunizing the host with an antigen through blood-feeding. In addition to a simple vaccine antigen, a flying vaccinator may potentially load a live attenuated microbe with an appropriate mechanism for sustaining its constitutive proliferation in the insect. In this study, a recombinant vesicular stomatitis virus (VSV) lacking the glycoprotein gene (VSV-G) was used to produce replication-restricted VSV (rrVSV) containing GFP. Transgenic Anopheles stephensi mosquitoes, in which the salivary glands expressed a VSV-G gene driven by an aapp salivary gland-specific promoter, were generated and injected intraperitoneally with rrVSV. The injected rrVSV entered the cells of the salivary gland and stimulated endogenous production of progeny rrVSV particles, as seen in rrVSV-infected Drosophila melanogaster expressing VSV-G. These data suggested the possibility of developing a valuable tool for delivering genetically attenuated virus vaccines via mosquito saliva, although efficient replication-restricted virus production is required.